Human iPSC-derived cardiomyocytes and pyridyl-phenyl mexiletine analogs. (15th August 2021) - Johnson, Mark; Gomez-Galeno, Jorge; Ryan, Daniel; Okolotowicz, Karl; McKeithan, Wesley L.; Sampson, Kevin J.; Kass, Robert S.; Mercola, Mark; Cashman, John R.
Graphical abstract: Highlights: Mexiletine is currently used as an antiarrhythmic drug but has limitations. LQT3 patient-induced pluripotent stem cell (iPSC)-derived cardiomyocytes (CMs) used. iPSC-derived CMs helped identify mexiletine analogs with drug-like properties. Medicinal chemistry optimization of substituted pyridyl phenyl mexiletine resulted. Mexiletine analogs were selective for Na over the K channel and for late over peak Na current. Abstract: In the United States, approximately one million individuals are hospitalized every year for arrhythmias, making arrhythmias one of the top causes of healthcare expenditures. Mexiletine is currently used as an antiarrhythmic drug but has limitations. The purpose of this work was to use normal and Long QT syndrome Type 3 (LQTS3) patient-derived human induced pluripotent stem cell (iPSC)-derived cardiomyocytes to identify an analog of mexiletine with superior drug-like properties. Compared to racemic mexiletine, medicinal chemistry optimization of substituted racemic pyridyl phenyl mexiletine analogs resulted in a more potent sodium channel inhibitor with greater selectivity for the sodium over the potassium channel and for late over peak sodium current.